A numerical solver for coupled dynamic simulation of glacial ice impacts considering hydrodynamic-ice-structure interaction. (15th April 2021) - Yu, Zhaolong; Amdahl, Jørgen
Abstract: Glacial ice features pose great threats on the safety of ships and offshore structures in the arctic. House sized bergy bits or growlers are of particular concern because of the detection capability limits of marine radars. Analysis and design of structures against collisions from such glacial ice bodies has always been challenging due to the complicated hydrodynamic-ice-structure interaction. This paper proposes a numerical solver for coupled simulation of glacial ice impacts accounting for the effects of hydrodynamic-ice-structure interaction. The solver adopts user subroutines provided in LS-DYNA and combines three different modules, i.e. the BWH (Bressan-Williams-Hill) criterion for the prediction of fracture of steels, a hydrostatic pressure dependent plasticity-based material model for constitutive modelling of ice, and the linear potential flow theory for hydrodynamic loads. The proposed solver is verified and calibrated to ice resistance data from field tests and is then applied to simulate ice collisions on a semi-submersible platform column. Collision scenarios with both in-plane 3DOF and full 6DOF ice motions are considered. The results are discussed with respect to ice motion trajectories, ice crushing and structural damage under the combined action of ice indentation and sliding loads. The dissipated energy predicted by external dynamic models is compared with simulation results and discussed. Highlights: A numerical solver is proposed for coupled dynamic simulation of glacial ice impacts accounting for the effects of hydrodynamic-ice-structure interactions. The proposed solver is verified and shown to be able to simulate the complicated hydrodynamic-ice-structure interactions in different collision scenarios with good efficiency and accuracy. An example application of the solver is carried out to simulate ice collisions on a semi-submersible platform column. The structures are found to be more vulnerable to combined ice indentation and sliding loads. A motion locking effect is found, which increases considerably the dissipated internal energy compared to that predicted by external dynamic models.